88.1k views
24 votes
Problem 4: Solve the initial value problem


y' = (y + 1)(y - 2)

y(0) = 1


Problem 4: Solve the initial value problem y' = (y + 1)(y - 2) y(0) = 1 ​-example-1

1 Answer

1 vote

Separate the variables:


y' = (dy)/(dx) = (y+1)(y-2) \implies \frac1{(y+1)(y-2)} \, dy = dx

Separate the left side into partial fractions. We want coefficients a and b such that


\frac1{(y+1)(y-2)} = \frac a{y+1} + \frac b{y-2}


\implies \frac1{(y+1)(y-2)} = (a(y-2)+b(y+1))/((y+1)(y-2))


\implies 1 = a(y-2)+b(y+1)


\implies 1 = (a+b)y - 2a+b


\implies \begin{cases}a+b=0\\-2a+b=1\end{cases} \implies a = -\frac13 \text{ and } b = \frac13

So we have


\frac13 \left(\frac1{y-2} - \frac1{y+1}\right) \, dy = dx

Integrating both sides yields


\displaystyle \int \frac13 \left(\frac1{y-2} - \frac1{y+1}\right) \, dy = \int dx


\frac13 \left(\ln|y-2| - \ln|y+1|\right) = x + C


\frac13 \ln\left|(y-2)/(y+1)\right| = x + C


\ln\left|(y-2)/(y+1)\right| = 3x + C


(y-2)/(y+1) = e^(3x + C)


(y-2)/(y+1) = Ce^(3x)

With the initial condition y(0) = 1, we find


(1-2)/(1+1) = Ce^(0) \implies C = -\frac12

so that the particular solution is


\boxed{(y-2)/(y+1) = -\frac12 e^(3x)}

It's not too hard to solve explicitly for y; notice that


(y-2)/(y+1) = ((y+1)-3)/(y+1) = 1-\frac3{y+1}

Then


1 - \frac3{y+1} = -\frac12 e^(3x)


\frac3{y+1} = 1 + \frac12 e^(3x)


\frac{y+1}3 = \frac1{1+\frac12 e^(3x)} = \frac2{2+e^(3x)}


y+1 = \frac6{2+e^(3x)}


y = \frac6{2+e^(3x)} - 1


\boxed{y = (4-e^(3x))/(2+e^(3x))}

User Jacob Nordfalk
by
4.6k points